Power system SCADA and smart grids - Thomas, Mini S.; McDonald, John D. (CRC Press, Taylor & Francis Group, 2015)
Power System SCADA and Smart Grids is designed to assist electrical engineering students, researchers, and practitioners alike in acquiring a solid understanding of SCADA systems and application functions in generation, transmission, and distribution systems, which are evolvingday by day, to help them adapt to new challenges effortlessly.